Why Does Nitriding of Grain‐Oriented Silicon Steel Become Slower at Higher Temperature?. Issue 4 (15th January 2021) - Guo, Qinyi; Li, Xianhao; Gong, Peng; Nutter, John; Rainforth, William Mark; Luo, Haiwen
Abstract : The nitriding process plays an essential role in the production of grain‐oriented silicon steel (GOSS) via the acquired‐inhibitor process. It is surprising at first glance to find that the increase of temperature from 840 to 930 °C retards the nitriding of GOSS rather than accelerating it. By both extensive microstructural characterization and thermodynamic calculations, this is attributed to the formation of austenite at high temperature in the oxidization layer, in which N atoms diffuse at a much lower rate than in ferrite. It is concluded that there exists an upper‐limit temperature for the efficient nitriding of GOSS, which is determined by both the preceding decarburization process and the nitriding atmosphere. Abstract : Higher temperature retards the nitriding of grain‐oriented silicon steel (GOSS), which is attributed to the new finding that austenite could appear during nitriding at 930 °C even in the case of C‐free high‐Si steel. Therefore, there exists an upper‐limit temperature for the efficient nitriding of GOSS.